Making Trade an Engine of Growth for All : The Case for Trade and for Policies to Facilitate Adjustment - International Monetary Fund; World Bank; World Trade Organization (World Bank, Washington, DC, 2017)
Longstanding tension between the benefits of open commerce and public support for it has become particularly salient today. G20 leaders pledged to work harder to build an open world economy and to promote greater inclusiveness. They called for action to communicate better the benefits of open markets to the wider public and for domestic policies to distribute those benefits more widely. G20 leaders saw the issue not as a tradeoff between openness and inclusiveness, but as a challenge to achieve more of both. Improved domestic policies and further trade reform can stimulate growth that is more inclusive. Addressing the source of discontent is important in its own right and also critical to shoring up support for trade. This paper draws on a wide range of recent policy analysis. Existing studies from international organizations provide greater depth in a number of areas that goes beyond what is possible in the present paper. Throughout the paper, references to key pieces of research and policy analysis from academics, think tanks, and international organizations help to document the statements made and provide options for readers who wish to delve into certain topics. Lessons are also drawn from country experience.